Eksistensi Desa Agraris - Budiman Budiman; Jumansyah Jumansyah; Sry Reski Mulka; Rinda Eka Santi (Kanal: Jurnal Ilmu Komunikasi, 2019)
The existence of an agrarian village is an integral part of sustainable regional development. The existence of Mulawarman Village as an agrarian village is the responsibility of the regional government as a dynamic / motivator of the people's aspirations, to support and protect and preserve agrarian villages. The existence of Mulawarman Village as an agrarian village is in fact still a major problem for the local government and the people in the village. This is due to the suboptimal role of the local government as a dynamic to move the aspirations of rural communities in carrying out development in the village. So that the existence of Mulawarma Village as an agrarian village is endangered.